2018
DOI: 10.1016/s2095-3119(18)61925-2
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual changes in the aggregate-size distribution and associated carbon of soil and their effects on the straw-derived carbon incorporation under long-term no-tillage

Abstract: Converting from conventional tillage to no-tillage influences the soil aggregate-size distribution and thus soil organic carbon (SOC) stabilization. However, the dynamics of soil aggregation and the straw-derived carbon(C) incorporation within aggregate fractions are not well understood. An experiment was established in 2004 to test the effects of two treatments, no-tillage with residue (NT) and conventional tillage without residue (CT), on the soil aggregate-size distribution and SOC stabilization in a contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The increase in saturated hydraulic conductivity on CT is expected to be short‐term with consecutive decreases through course of the vegetative season (Kool et al., 2019). Similar findings on significantly low saturated hydraulic conductivity values on consolidated CT soils have been previously reported (Park & Smucker, 2005; Yin et al., 2018). Findings here suggest that the high instabilities in saturated hydraulic conductivity on OT and CT were caused by negative effects of disruptions on the soil's natural porosity compared with RT and NT.…”
Section: Resultssupporting
confidence: 90%
“…The increase in saturated hydraulic conductivity on CT is expected to be short‐term with consecutive decreases through course of the vegetative season (Kool et al., 2019). Similar findings on significantly low saturated hydraulic conductivity values on consolidated CT soils have been previously reported (Park & Smucker, 2005; Yin et al., 2018). Findings here suggest that the high instabilities in saturated hydraulic conductivity on OT and CT were caused by negative effects of disruptions on the soil's natural porosity compared with RT and NT.…”
Section: Resultssupporting
confidence: 90%
“…The elastic hysteresis time of NT paddy soil was prolonged; thus, the suitable tillage period of paddy soil could be prolonged by increasing soil organic matter. Relevant studies have shown that straw is rich in carbon content, and the decomposition of straw after returned to the field will form pores, thereby increasing soil porosity and activated carbon content [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, research on the influence of tillage methods on farmland soil mostly focuses on the physical properties of soil topsoil, such as the dynamic effect of farming systems on soil carbon and nitrogen in southern Brazil [ 24 ]. For instance, Yin et al [ 25 ] suggested that no tillage ridge cultivation could thicken the tillage layer, reduce soil disturbance, promote the formation of large aggregates, and improve soil structure and physical-chemical properties. Research on the influence of moisture content on soil mainly examines agricultural water, soil engineering and soil-machine dynamics, including studies on field soil compaction by machines [ 26 , 27 ] and on field water, soil conservation, and soil strength [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organic materials can support the formation of more stable soil aggregate through organic polymer bonds with soil particles (Kogel-Knabner and Amelung, 2014). Soil aggregate stability highly depends on the soil texture, the content of clay fraction, the content of organic matter, the soil tillage, and the type of land use (Zhang et al, 2017; 1-month 4-month Zhao et al, 2017;Minasny and Mcbratney, 2018;Yin et al, 2018).…”
Section: Stability Of Soil Aggregatesmentioning
confidence: 99%